Combining Geographic Information Systems and Agent-Based Models in Archaeology: Part 2 of 3. Issue 2 (22nd May 2019) - Davies, Benjamin; Romanowska, Iza; Harris, Kathryn; Crabtree, Stefani A.
ABSTRACT: Archaeologists are using spatial data in increasingly sophisticated analyses and invoking more explicit considerations of space in their interpretations. Geographic information systems (GIS) have become standard technology for professional archaeologists in the collection and management of spatial data. Many calls have been made to develop and adapt digital geospatial technologies for interpretation and understanding past social dynamics, but this has been limited to some extent by the static nature of map-oriented GIS approaches. Here, we illustrate how coupling GIS with agent-based modeling (ABM) can assist with more dynamic explorations of past uses of space and geospatial phenomena. Abstract : Los arqueólogos están usando datos espaciales en análisis cada vez más sofisticados y tomando en cuenta consideraciones más específicas en sus interpretaciones. Los sistemas de información geográficas (SIG) se han convertido en una tecnología estándar para los arqueólogos profesionales a la hora de recolectar y gestionar datos espaciales. Muchos llamaron la atención sobre la necesidad de desarrollar y adaptar tecnologías geoespaciales digitales para la interpretación y comprensión de las dinámicas sociales del pasado pero, sin embargo, se han limitado a un enfoque SIG basado en la recreación de mapas. Aquí ilustramos como la combinación de SIG con el modelado basado en agentes (ABM) puede ayudar a desarrollar exploraciones más dinámicas sobre el uso del espacio y los fenómenos geoespaciales del pasado.